Higher-Order Organizational Commitment Instrument Integrating Spiritual and Islamic Educational Values: Development and CVA-Based Analysis - Amaliyah; Nisak Ruwah Ibnatur Husnul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and validate a higher-order organizational commitment instrument integrating spiritual dimensions and Islamic educational values, grounded in the three-dimensional model proposed by John P. Meyer and Natalie J. Allen (Affective, Continuance, and Normative Commitment), with the addition of a spiritual-value dimension reflecting Islamic educational principles. A quantitative research design was employed involving 100 lecturers at Universitas Pamulang selected through simple random sampling. The initial instrument consisted of 24 items proportionally distributed across three dimensions, with a balanced composition of favorable and unfavorable statements. Data were analyzed using Second-Order Confirmatory Factor Analysis (CFA) with SmartPLS 4, alongside Content Validity Analysis (CVA) to ensure item relevance and representativeness. The findings indicate that the higher-order construct demonstrated satisfactory convergent validity, with factor loadings exceeding 0.50 and Average Variance Extracted (AVE) values above 0.50 across dimensions. Affective Commitment demonstrated the strongest contribution to the higher-order construct, followed by Continuance Commitment and Normative Commitment. Reliability analysis confirmed strong internal consistency, with Cronbach’s alpha and Composite Reliability exceeding recommended thresholds. The developed instrument is empirically valid and reliable for assessing organizational commitment among lecturers in value-based higher education settings and contributes to the advancement of psychometric measurement by integrating organizational theory with spiritual and Islamic educational values.